A Multi‐Purpose Heliophysics L4 Mission - A. Posner; C. N. Arge; J. Staub; O. C. StCyr; D. Folta; S. K. Solanki; R. D. T. Strauss; F. Effenberger; A. Gandorfer; B. Heber; C. J. Henney; J. Hirzberger; et al. (Space Weather)
Abstract The Earth‐Sun Lagrangian point 4 is a meta‐stable location at 1 AU from the Sun, 60° ahead of Earth's orbit. It has an uninterrupted view of the solar photosphere centered on W60, the Earth's nominal magnetic field connection to the Sun. Such a mission on its own would serve as a solar remote sensing observatory that would oversee the entire solar radiation hemisphere with significant relevance for protecting Moon and Mars explorers from radiation exposure. In combination with appropriately planned observatories at L1 and L5, the three spacecraft would provide 300° longitude coverage of photospheric magnetic field structure, and allow continuous viewing of both solar poles, with >3.6° elevation. Ideally, the L4 and L5 missions would orbit the Sun with a 7.2° inclination out of the heliographic equator, 14.5° out of the ecliptic plane. We discuss the impact of extending solar magnetic field observations in both longitude and latitude to improve global solar wind modeling and, with the development of local helioseismology, the potential for long‐term solar activity forecasting. Such a mission would provide a unique opportunity for interplanetary and interstellar dust science. It would significantly add to reliability of operational observations on fast coronal mass ejections directed at Earth and for human Mars explorers on their round‐trip journey. The L4 mission concept is technically feasible, and is scientifically compelling.